Análise da ocorrência de metástase intraocular e pulmonar em cadelas portadoras de carcinoma mamário e correlação com mutação e expressão de E-caderina - Pardini, Luciana Moura Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: E-cadherin is a transmembrane protein, encoded by CDH1 gene, that has an important role in intercellular adhesion of epithelial tissues. Loss of function or decreased expression of E-cadherin may lead to cancer progression and metastasis. In mammary epithelial neoplasms, lung metastases occur more frequently, but the ocular metastasis, especially in the choroid, are relatively common but underdiagnosed clinically. Methods: Twenty-eight dogs of different breeds, non-castrated, older than five years, diagnosed with breast cancer by cytopathological examination, without pulmonary and/or ocular metastasis, have undergone to radical mastectomy and ovariosalpingohisterectomy (OSH), and re-evaluated after three and six months postoperatively. The pattern of relative expression of CDH1 gene in normal and tumor tissues was assessed by TaqMan Universal PCR Master Mix system; the pattern of methylation was performed using MSP-PCR; DNA sequencing analysis of mutations and polymorphisms were performed from peripheral blood using the termination chain reaction technique with BigDye Terminator v.3 Cycle Sequencing kit. Immunohistochemical analyzes were performed to evaluate the expression of E-cadherin. Results: None of the 28 dogs studied had ocular or pulmonary metastasis with 3 or 6 months postoperatively. In 57,1% of cases a decreased relative expression of CDH1 gene was identified. In 100% of cases there was methylated status for the CDH1 gene, confirming the hypothesis that non-tumor cells can contribute to these results. In 46,5% of the cases reduced E-cadherin expression by immunohistochemistry was identified. Three tumor histotypes were identified: complex carcinoma, tubulopapillary, and carcinoma in mixed tumor. In 100% of cases of tubulopapillary carcinoma was identified a reduced gene expression of CDH1 by both qPCR and by immunohistochemistry. The sequencing of the gene, 6 animals (21,4%) had silent mutations in exons 3, 7 ...

Introdução: A E-caderina é uma proteína transmembranosa, codificada pelo gene CDH1, que desempenha um papel importante na adesão intercelular de tecidos epiteliais. A perda da função ou expressão diminuída de E-caderina pode implicar em metástases e progressão do câncer. Nas neoplasias mamárias, metástases pulmonares ocorrem com maior frequência, porém as metástases oculares, especialmente na coroide, são relativamente comuns, mas pouco diagnosticadas clinicamente. Metodologia: Vinte e oito cadelas de diferentes raças, não-castradas, com idade superior a 5 anos, com diagnóstico de carcinoma mamário ao exame citopatológico, sem metástases pulmonares e/ou oculares, foram submetidas à mastectomia radical e ovariosalpingohisterectomia (OSH), sendo reavaliadas após três e seis meses de pós-operatório. O padrão de expressão relativa do gene CDH1 em tecidos tumorais e normais, foi avaliado pelo sistema TaqMan Universal PCR Master Mix; o padrão de metilação foi realizado utilizando-se a técnica de MSP-PCR; o sequenciamento do DNA, análise das mutações e polimorfismos foram realizados a partir do sangue periférico, utilizando-se a técnica de reação de terminação em cadeia pelo kit BigDye Terminator v.3 Cycle Sequencing. Análises imunohistoquímicas foram realizadas para avaliar a expressão da E-caderina. Resultados: Nenhuma das 28 cadelas estudadas apresentou metástase ocular ou pulmonar com três ou seis meses de pós-operatório. Em 57,1% dos casos uma menor expressão relativa do gene CDH1 foi identificada. Em 100% dos casos verificou-se o status metilado para o gene CDH1, reafirmando a hipótese de que células não-tumorais podem contribuir para estes resultados. Em 46,5% dos casos identificou-se expressão reduzida de E-caderina pela técnica de imunohistoquímica. Foram identificados 3 histotipos tumorais: carcinoma complexo, tubulopapilífero e carcinoma em tumor misto. Em 100% dos casos de carcinoma...
Analysis of intraocular and pulmonary metastasis in female dogs suffering from mammary carcinoma and correlation with E-cadherin mutation and expression
Keywords: Mamas - Doenças; Cães - Doenças; Moleculas de adesão celular; Metastase; Breast - Diseases